Does Medical Presence Decrease the Perceived Risk of Substance-Related Harm at Music Festivals?. Issue Volume 34:Issue s1(2019) (May 2019) - Munn, Matthew Brendan; White, Melissa Sydney; Hutton, Alison; Turris, Sheila; Tabb, Haddon; Lund, Adam; Ranse, Jamie
Abstract : Introduction: The use of recreational substances is a contributor to the risk of morbidity and mortality at music festivals. One of the aims of onsite medical services is to mitigate substance-related harms. It is known that attendees' perceptions of risk can shape their planned substance use; however, it is unclear how attendees perceive the presence of onsite medical services in evaluating the risk associated with substance use at music festivals. Methods: A questionnaire was administered to a random sample of attendees entering a multi-day electronic dance music festival. Results: There were 630 attendees approached and 587 attendees completed the 19 item questionnaire. Many confirmed their intent to use alcohol (48%, n=280), cannabis (78%, n=453), and recreational substances other than alcohol and cannabis (93%, n=541) while attending the festival. The majority (60%, n=343) stated they would still have attended the event if there were no onsite medical services available. Some attendees agreed that the absence of medical services would have reduced their intended use of alcohol (30%, n=174) and recreational substances other than alcohol and cannabis (46%, n=266). Discussion: In the context of a music festival, plans for recreational substance use appear to be substantially altered by attendees' knowledge about the presence or absence of onsite medical services. This contradicts our initial hypothesis that medical services are independent of planned substance use and serve solely to reduce any associated harms. Additional exploration and characterization of this phenomenon at various events would further clarify the understanding of perceived risks surrounding substance use and the presence of onsite medical services.